Serum Myonectin Correlates with Abdominal Adiposity but not with Serum or Intramuscular Lipids in Adults (2023)
ABSTRACT: Myonectin is a myokine that has favorable effects on serum lipid regulation in murine models, but human studies have shown conflicting results. Also, the function of myonectin in humans can be more comprehensively addressed by extending the analysis to its relationship with the accumulation of lipids in natural and ectopic depots. PURPOSE: To assess the relationship between serum myonectin and lipids in three different compartments, named, serum, global and regional fat mass, and intramuscular lipid content, in adults with metabolic risk factors. METHODS: Cross-sectional study carried out in adults who met at least one metabolic criterion of the metabolic syndrome (MS). Serum myonectin was determined by enzyme-linked immunosorbent assay, lipid profile by conventional techniques and free fatty acids by gas chromatography. Total and regional fat mass was studied by dual-energy X-ray absorptiometry. Intramuscular lipid (intramyocellular (IMCL) and extramyocellular (EMCL)) content was assessed through proton nuclear magnetic resonance spectroscopy in the right vastus lateralis muscle. RESULTS: The subjects (n = 90) had a (median (interquartile range)) age of 51.5 (46.0–56.0) years, 71% of which were women. The whole sample had a serum myonectin of 1.08 (0.89–1.48) ng·mL-1, triglycerides (mean ± standard deviation) of 167.8 ± 91.9 mg·dL-1, high density lipoproteins of 46.7 ± 11 mg·dL-1, low density lipoproteins of 146.2 ± 46.8 mg·dL-1, palmitic acid of 0.196 ± 0.108 μg·dL-1 and stearic acid of 0.096 ± 0.058 μg·dL-1. Their body mass index was 29.4 ± 4.2 kg·m-2, fat mass index 11.1 ± 3 kg·m-2 and android/gynoid ratio 0.58 ± 0.17. IMCL, EMCL and total intramuscular lipids were 9.5 (5.7-13.9), 28.1 (19.7-42.5) and 40.6 (27.9-59.6) mmol·kg-1 ww, respectively. Multiple linear regression models adjusted for age, sex, fat mass index and lean mass index showed that myonectin was negatively correlated only with the android/gynoid ratio (R2 = 0.48, P < 0.01), but not with any other variable of the study. CONCLUSION: Myonectin may have a role in the pathophysiology of the MS by negatively regulating the accumulation of fat in abdominal depots.